Combinatorial actions of Tgfβ and Activin ligands promote oligodendrocyte development and CNS myelination - Dutta, Dipankar J. (The Company of Biologists, 2014)
In the embryonic CNS, development of myelin-forming oligodendrocytes is limited by bone morphogenetic proteins, which constitute one arm of the transforming growth factor-β (Tgfβ) family and signal canonically via Smads 1/5/8. Tgfβ ligands and Activins comprise the other arm and signal via Smads 2/3, but their roles in oligodendrocyte development are incompletely characterized. Here, we report that Tgfβ ligands and activin B (ActB) act in concert in the mammalian spinal cord to promote oligodendrocyte generation and myelination. In mouse neural tube, newly specified oligodendrocyte progenitors (OLPs) are first exposed to Tgfβ ligands in isolation, then later in combination with ActB during maturation. In primary OLP cultures, Tgfβ1 and ActB differentially activate canonical Smad3 and non-canonical MAP kinase signaling. Both ligands enhance viability, and Tgfβ1 promotes proliferation while ActB supports maturation. Importantly, co-treatment strongly activates both signaling pathways, producing an additive effect on viability and enhancing both proliferation and differentiation such that mature oligodendrocyte numbers are substantially increased. Co-treatment promotes myelination in OLP-neuron co-cultures, and maturing oligodendrocytes in spinal cord white matter display strong Smad3 and MAP kinase activation. In spinal cords of ActB-deficient Inhbb(−/−) embryos, apoptosis in the oligodendrocyte lineage is increased and OLP numbers transiently reduced, but numbers, maturation and myelination recover during the first postnatal week. Smad3(−/−) mice display a more severe phenotype, including diminished viability and proliferation, persistently reduced mature and immature cell numbers, and delayed myelination. Collectively, these findings suggest that, in mammalian spinal cord, Tgfβ ligands and ActB together support oligodendrocyte development and myelin formation.